Challenges, stressors, and resilience resources experienced by older black women in Rural South Carolina throughout the COVID-19 pandemic - Arielle N’Diaye; Camryn Garrett; Sara Wilcox; Bankole Olatosi; Xiaoming Li; Shan Qiao (PLoS ONE, 2026)
Background Resilience has been established as a protective factor against mental health challenges (e.g., anxiety, depression). From an intersectional perspective, the stressors experienced by Black women living in rural communities are likely to have been exacerbated during the COVID-19 pandemic. This study aims to identify the challenges and stressors experienced and the resilience resources available to and relied upon by rural, Black women, during the pandemic. Methods Individual, in-depth, structured interviews (n = 24) were conducted among Black women living in rural South Carolina, recruited by local community health workers, from January to April of 2024. All interviews were recorded, uploaded to a password-protected online drive, transcribed using Otter.ai, and verified for verbatim transcription. The data were analyzed using an abductive approach where the data were inductively coded following a thematic analysis approach and were then deductively situated within a socioecological model. Results Participants shared challenges and stressors (i.e., anxiety, depression, isolation, grief, visitation limitations, employment changes, increased cost of living, structural and systemic inequity, and limited access to mental healthcare) experienced throughout the pandemic. Resilience resources were also identified at the individual (i.e., religion and faith, self-care), interpersonal (i.e., generational knowledge of preparedness, social connection), organizational (i.e., workplace and religious institution pandemic policy adaptation), community (i.e., rural community norms, trusted community messengers, food and supply drives), and structural levels (i.e., emergency SNAP enrollment, stimulus checks) of the socioecological model. Conclusions The present results suggest that interventions, designed to prepare and respond to public health emergencies, should leverage and amplify existing community-led resilience resources, thereby adequately tailoring efforts and ensuring they meet the needs identified by community members.